Microwave pyrolysis of biomass for bio-oil production: Scalable processing concepts - Beneroso, Daniel; Monti, T.; Kostas, E.T.; Robinson, J. (Elsevier, 2017)
The pursuit of sustainable hydrocarbon alternatives to fossil fuels has prompted an acceleration in the development of new technologies for biomass processing. Microwave pyrolysis of biomass has long been recognised to provide better quality bio-products in shorter timescales compared to conventional pyrolysis. Although this topic has been widely assessed and many investigations are currently ongoing, this article gives an overview beyond the physico-chemical pyrolysis process and covers engineering aspects and the limitations of microwave heating technology. Herein, we provide innovative scalable concepts to perform the microwave pyrolysis of biomass on a large scale, including essential energy and material handling requirements. Furthermore, some of the possible socio-economic and environmental implications derived from the use of this technology in our society are discussed. Such potential concepts are expected to assist the needs of the industrial bioenergy community to move this largely studied process upwards in scale.